Effectiveness of Landslide Disaster Education on Students' Knowledge and Attitudes at SMP Negeri 31 Medan Tuntungan - Meutia Nanda; Icha Agustien; Febby Maharani; Annisa Sandy; Adinda Jeane; Nurhayati Mahdiyyah; Maya Simbolon (ALACRITY : Journal of Education, 2026)
Landslides are natural events involving the movement of soil and/or rock material from its original position to a lower part of the slope due to a decrease in the slope's bearing capacity. They are influenced by high rainfall intensity, slope conditions, soil characteristics, and changes in physical environmental conditions due to human activity. Disaster education in schools plays an important role in shaping knowledge and attitudes of preparedness for landslides. This study aims to determine the effectiveness of landslide disaster education on the knowledge and attitudes of students at SMP Negeri 31 Medan Tuntungan. This study used a quantitative method with a One-Group Pre-test Post-test design on 33 ninth-grade students. The Chi-Square test results showed a significant difference in the proportion of categories, where the number of students with “Good” knowledge increased from 54.5% to 84.8% (p=0.039), and “Good” attitudes increased from 42.4% to 75.8% (p=0.007). However, analysis using the Paired Sample t-test showed that individually, there was no significant increase in the average knowledge score (from 47.96 to 49.44; p=0.303) and no significant change in the average attitude score (from 55.26 to 54.07; p=0.268). Not statistically significant. The absence of a significant effect on these absolute scores is thought to be due to a ceiling effect, whereby students' basic understanding was already quite high from the outset, and a one-way educational method that was unable to profoundly change the affective domain in a short period of time. A more participatory, routine educational program involving hands-on practice is needed to strengthen students' disaster preparedness.